Univariate and Simplex Optimization for the Spectrophotometric Determination of Cimetidine and Erythromycin ethylsuccinate Drugs Using Bromothymol Blue Via Ion-Pair Formation - Dikran, S. B.; Mohammed, A. K.; Al-Jumaily, A. K.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The ion-pair formation method has been applied for the spectrophotometric determination of Cimetidine and Erythromycin ethylsuccinate, in bulk samples and in dosage form. The methods are accurate, simple, rapid, inexpensive and sensitive depending on the extraction of the formed ion-pair with brompthymol blue (BTB) as a chromogenic reagent in chloroform, use phthalate buffer of pH 5.5 and 4.0 for Cimetidine and Erythromycin ethylsuccinate respectively. The formed complexes show absorbance maxima at 427.5 nm and 414.5 nm for Cimetidine and Erythromycin ethylsuccinate respectively against reagent blank. The calibration graphs are linear in the ranges of 0.5-15 µg.mL-1 with detection limit of 0.222 µg.mL-1 for Cimetidine and 0.5-50 µg.mL-1 with detection limit of 0.286 µg.mL-1 for Erythromycin ethylsuccinate. The results show the absence of interferences from the excipients on the determination of these drugs. The proposed methods have been successfully applied for the determination of Cimetidine and Erythromycin ethylsuccinate (with two of its derivatives) in pharmaceutical preparations.